2014
DOI: 10.1128/aac.03501-14
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in mmpL and in the Cell Wall Stress Stimulon Contribute to Resistance to Oxadiazole Antibiotics in Methicillin-Resistant Staphylococcus aureus

Abstract: Staphylococcus aureus is a leading cause of hospital-and community-acquired infections, which exhibit broad resistance to various antibiotics. We recently disclosed the discovery of the oxadiazole class of antibiotics, which has in vitro and in vivo activities against methicillin-resistant S. aureus (MRSA). We report herein that MmpL, a putative member of the resistance, nodulation, and cell division (RND) family of proteins, contributes to oxadiazole resistance in the S. aureus strain COL. Through serial pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
4
5
0
2
Order By: Relevance
“…In addition to our own work, which supports a role for FarE as an efflux pump, other researchers using a different approach with S. aureus COL demonstrated that an amino acid substitution in FarE (SACOL2566) promotes resistance to a newly described oxadiazole family of antibiotics (61). In E. coli, polymorphisms that cause amino acid substitutions in AcrB can also accrue during in vitro selection of strains that are resistant to fluoroquinolone antibiotics (62), and in these examples, it is likely that resistance is due to amino acid substitutions that expand the substrate specificity of the efflux pump (61,62). However, although AcrB family efflux pumps have been most extensively characterized as mediators of multidrug resistance, we contend that the primary function of FarE is to promote efflux of antimicrobial fatty acids that would be encountered during colonization or within a tissue abscess.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In addition to our own work, which supports a role for FarE as an efflux pump, other researchers using a different approach with S. aureus COL demonstrated that an amino acid substitution in FarE (SACOL2566) promotes resistance to a newly described oxadiazole family of antibiotics (61). In E. coli, polymorphisms that cause amino acid substitutions in AcrB can also accrue during in vitro selection of strains that are resistant to fluoroquinolone antibiotics (62), and in these examples, it is likely that resistance is due to amino acid substitutions that expand the substrate specificity of the efflux pump (61,62). However, although AcrB family efflux pumps have been most extensively characterized as mediators of multidrug resistance, we contend that the primary function of FarE is to promote efflux of antimicrobial fatty acids that would be encountered during colonization or within a tissue abscess.…”
Section: Discussionsupporting
confidence: 73%
“…As with many proteins that possess an N-terminal TetR DNA binding domain, protein structural modeling and homology searches indicate that FarR belongs to the TetR/AcrR family of regulators, while FarE belongs to the RND family of multidrug efflux pumps, which include AcrB. In addition to our own work, which supports a role for FarE as an efflux pump, other researchers using a different approach with S. aureus COL demonstrated that an amino acid substitution in FarE (SACOL2566) promotes resistance to a newly described oxadiazole family of antibiotics (61). In E. coli, polymorphisms that cause amino acid substitutions in AcrB can also accrue during in vitro selection of strains that are resistant to fluoroquinolone antibiotics (62), and in these examples, it is likely that resistance is due to amino acid substitutions that expand the substrate specificity of the efflux pump (61,62).…”
Section: Discussionsupporting
confidence: 70%
“…Notably,t he compound class was identified by in silico screening against the Xray structure of PBP2a. [172] Additional comprehensive SAR studies revealed the oxadiazole 75 b( Figure 11) to have as imilar potencya so xadiazole 3i nvitro,w hile having at hreefold reduced toxicity in HepG2 cells (IC 50 of 25.8 mgmL À1 versus 75.7 mgmL À1 ,r espectively). However,all the compounds were inactive against Gram-negative pathogens.…”
Section: Oxadiazolesmentioning
confidence: 98%
“…Interessanterweise wurde diese Substanzklasse durch ein In-silico-Screening auf Grundlage der Kristallstruktur von PBP2a entdeckt. [172] Zusätzliche umfassende SAR-Studien führten zu Oxadiazol 75 b (Abbildung 11), das in vitro eine ähnliche Wirksamkeit wie Oxadiazol 3besitzt, aber dreifach weniger toxisch in HepG2-Zellen ist (IC 50 von 25.8 mgmL À1 vs.7 5.7 mgmL À1 ). Die Verbindung hat ausgezeichnete Wirksamkeit gegen eine Reihe von Gram-positiven Bakterien (u. a. Linezolid-und Va ncomycin-resistente MRSA sowie VRE:M IC von 2 mgmL À1 ).…”
Section: Oxadiazoleunclassified
“…Übereinstimmend mit früheren Ergebnissen konnten die Mutationen auf strukturelle Gene und Promotoren der Gene für das Zellwand-Stress-Stimulon zurückgeführt werden. [172] Zusätzliche umfassende SAR-Studien führten zu Oxadiazol 75 b (Abbildung 11), das in vitro eine ähnliche Wirksamkeit wie Oxadiazol 3besitzt, aber dreifach weniger toxisch in HepG2-Zellen ist (IC 50 von 25.8 mgmL À1 vs.7 5.7 mgmL À1 ). [173] Die Wirksamkeit in vivo wurde mithilfe eines MRSA-Peritonitis-Modells in der Maus untersucht, in dem die orale Gabe einer einzelnen Dosis von Oxadiazol 75 b äußerst effektiv war (ED 50 von 3.1 mg pro kg Kçrpergewicht, verglichen mit 2.8 mg pro kg fürL inezolid).…”
Section: Oxadiazoleunclassified